The professional meeting in december for librarians from the north of the Republic of Moldova (Confluenţe Bibliologice, 2024)
This article provides an account of the professional meeting organized by the USARB Scientiﬁc Library – Departmental Librarianship Center, which took place on December 17, 2024. The event brought together librarians from pre-university education institutions (schools, gymnasiums, and high schools) in the northern region of the Republic of Moldova and the municipality of Bălți. The meeting addressed key topics of great importance to the contemporary library ﬁeld, including the digital transformation of libraries, the implementation of best practices in managing educational resources, and the essential role of continuous education in professional development.
Keywords: Departmental Librarianship Center; school library